Nurses' COVID-19 Fears and Patient Safety Attitudes in the Pandemic - Efil, Sevda; TÜREN, SEVDA; Demir, Elif (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. The fear experienced by nurses during the COVID-19 pandemic may threaten patient safety. This study was conducted with the aim of examining nurses' COVID-19 fears and attitudes to patient safety in the pandemic. Material and methods. The research had a descriptive and cross-sectional design. The research sample consisted of 245 nurses working at a teaching and research hospital in Istanbul, Turkey's most populous province. Research data were collected in June-July 2021. A Nurse Characteristics Form, the Fear of COVID-19 Scale (FCV-19S) and the Patient Safety Attitude Questionnaire were used to collect data. The data evaluation was performed using descriptive statistics, Student t test, one-way variance (ANOVA), and Pearson correlation analysis. Results. The nurses' mean score for fear of COVID-19 was 16.67±6.88, and their mean score for patient safety attitude was 141.70±27.78. Their COVID-19 fear levels and mean patient safety attitude scores were found to differ according to their intention to leave the job, their education on COVID-19 and their age. Conclusion. Nurses' experiencing of physical, social and psychological problems relating to the COVID-19 pandemic should be followed up in the long term.
Keywords: Covid-19; Nurses; Patient Safety